Ir d-band derived superconductivity in the lanthanum-iridium system LaIr3. (6th November 2017) - Haldolaarachchige, Neel; Schoop, Leslie; Khan, Mojammel A; Huang, Wenxuan; Ji, Huiwen; Hettiarachchilage, Kalani; Young, David P
Abstract: The electronic properties of the heavy metal superconductor L a I r 3 are reported. The estimated superconducting parameters obtained from physical properties measurements indicate that L a I r 3 is a BCS-type superconductor. Electronic band structure calculations show that Ir d -states dominate the Fermi level. A comparison of electronic band structures of L a I r 3 and L a R h 3 shows that the Ir-compound has a strong spin–orbit-coupling effect, which creates a complex Fermi surface.